PEMBINAAN IMPLEMENTASI 4 METODE PENGHITUNGAN SERTA BAGIAN-BAGIAN AHLI WARIS BAGI SANTRI KELAS 6 MMU B-73 LOMBOK KULON - Ifan Afandy; Muhammad Husni (LPPM IAI Dar Aswaja Rokan Hilir, 2026)
The science of Mawaris or Faraidh is a science whose interest is decreasing every time. We have felt this together today, in fact this reality was conveyed specifically by the Prophet sallallaahu 'Alaihi Wasallam 1400 years ago. In the hadith narrated by Imam Ibn Majah number 2719, the Prophet said to Abu Hurairah which means: